Enhanced performance of dye-sensitized solar cells based on TiO2 nanotube membranes using an optimized annealing profile - Mohammadpour, F.; Moradi, M.; Lee, Kiyoung; Cha, Gi; So, Seulgi; Kahnt, Axel; Guldi, Dirk Michael; Altomare, Marco; Schmuki, Patrik (Chemical Communications, 2015)
We use free-standing TiO2 nanotube membranes that are transferred onto FTO slides in front-side illuminated dye-sensitized solar cells (DSSCs). We investigate the key parameters for solar cell arrangement of self-ordered anodic TiO2 nanotube layers on the FTO substrate, namely the influence of the annealing procedure on the DSSC light conversion efficiency. The results show that using an optimal temperature annealing profile can significantly enhance the DSSC efficiency (in our case extgreekh = 9.8%), as it leads to a markedly lower density of trapping states in the tube oxide, and thus to strongly improved electron transport properties.
EAM Import::2019-03-14